Correlation Between Lexical Richness and Overall Quality of Argumentative Essays Written by English Department Students - Rizky Lutviana; A. Effendi Kadarisman; Ekaning Dewanti Laksmi (Pascasarjana UM, 2015)
Abstract: This study aims at revealing the contribution of diction to the overall quality of argumenta-tive essays written by 42 EFL students. The researcher compared two sets of scores, the score of students’ lexical richness, measured with LFP (Lexical Frequency Profile), and the score of overall quality of EFL students’ argumentative essay, using analytical scoring rubric. The small and not significant correlation (ñ=.18, sig=.23) implied that diction had small contribution to the overall quality of the essay. There might be another factor related to the diction that supports the quality of written text. Thus, further research is needed to be conducted. Key Words: diction, lexical richness, overall quality, argumentative essayAbstrak: Penelitian ini bertujuan untuk menemukan kontribusi diksi untuk kualitas keseluruhan dari esai argumentatif yang ditulis oleh 42 siswa EFL. Peneliti membandingkan dua set nilai, skor siswa kekayaan leksikal, diukur dengan LFP (Lexical Frequency Profile), dan skor keseluruhan kualitas siswa EFL pada esai argumentatif, dengan menggunakan rubrik skoring analitis. Korelasi kecil dan tidak signifikan (ñ = 0,18, sig = 0,23) menunjukkan bahwa diksi memiliki kontribusi kecil untuk kualitas keseluruhan dari esai. Kemungkinan, ada faktor lain yang berhubungan dengan diksi yang mendukung kualitas dari teks. Dengan demikian, penelitian lebih lanjut diperlukan untuk dilakukan. Kata kunci: diksi, kekayaan leksikal, kualitas secara keseluruhan, esai argumentatif